Strategies to Improve Conceptual Cost Estimates Accuracy of Flyover Development in the Provincial Government of DKI Jakarta - Putika Yussi; Yusuf Latief (Journal of International Conference Proceedings (JICP), 2021)
This study identifies the dominant factors in the conceptual cost estimate process of flyover development in the Provincial Government of DKI Jakarta that affect accuracy, based on the relationship model between the conceptual cost estimation process of flyover development in the Provincial Government of DKI Jakarta with the accuracy. Furthermore, this study also develops strategies to improve the accuracy based on the dominant factors. Two parts of the method are used in this study. The first method is to obtain the dominant factors in estimating the conceptual cost of flyover development in the DKI Jakarta Provincial Government, which affects accuracy using the SEM-PLS method, which involved 151 respondents. Second, the method to obtain strategies to improve accuracy based on these dominant factors, using the gap analysis. The result shows that four dominant factors affect accuracy: information quality, project definition, cost information, and project characteristics. Improving strategies are obtained based on those identified dominant factors. The finding of this study suggests that these strategies can be compiled into the guideline of the conceptual cost estimate process, which can be a tool to assist relevant agency personnel in carrying out the stages in the process of conceptual cost estimation of flyover development.